PENGARUH PEMBERIAN KOMPOS KULIT KOPI DAN PUPUK NPK TERHADAP PERTUMBUHAN BIBIT KELAPA SAWIT (ElaeisguineensisJacq.) DI PEMBIBITAN UTAMA - Tumangger, Rinaldi Fransisko; Hapsoh, Hapsoh; Sukemi, Sukemi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The experiment aims to know the effect of interaction giving coffee pulp compost and NPK and get a good dose for the growth of oil palm seedlings in nurseries main. This research was carried out in the farm of Technical Implementation Unit Departement of Agrotechnology, University of Riau, from February to Juny 2016. The research was conducted experimentally using a completely randomized design factorial with two factors such as factor of coffee pulp compost (K) consists of 3 extents that are coffee pulp compost 0 g/plant (0 ton/ha), coffee pulp compost 50 g/plant (10 tons/ha) and coffee pulp compost 75 g/plant (15 tons/ha). The second factor is NPK consists of 4 extents that are NPK 0 g/plant, NPK 6,25 g/plant, NPK 12,5 g/plant and NPK 18,75 g/plant. Two factors obtained 12 combined treatment with 3 replications, so that there are 36 experimental units. Each experimental unit consisted of two plants, so there are 72 plants. Parameters measured were plant height increase, in the number of leaves, the increase in diameter tubers, seedling root volume and dry weight of seedlings.The result showed no interaction effect giving coffee pulp compost and NPK at oil palm seed Tenera varieties (DXP)Marihat age of 3-7 months to all parameters observed. Giving coffee pulp compost dose of 75 g/ plant (15 tons / ha) were able to increase the height increment of seeds as big as 1,09 % and dry weight of oil palm seedsTeneravarieties (DXP), Marihat age of 3-7 months. Key words : coffee pulp compost, NPK, oil palm seeds